Postoperative hypernatremia is associated with worse brain injuries on EEG and MRI following pediatric cardiac surgery - Lin, Rouyi; Du, Na; Feng, Jinqing; Li, Jianbin; Li, Xiaowei; Cui, Yanqin; Ning, Shuyao; Zhang, Mingjie; Huang, Guodong; Wang, Huaizhen; Chen, Xinxin; Ma, Li; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objectives Dysnatremia is a common electrolyte disturbance after cardiopulmonary bypass (CPB) surgery for congenital heart disease (CHD) and a known risk factor for adverse neurological events and clinical outcomes. The objective of this study was to evaluate the association of dysnatremia with worse abnormal EEG patterns, brain injuries detected by magnetic resonance imaging (MRI) and early adverse outcomes. Methods We monitored continuous EEG in 340 children during the initial 48 h following cardiac surgery. Demographics and clinical characteristics were recorded. Sodium concentrations were measured in the arterial blood gas analysis every 6 h. Hyponatremia and hypernatremia were classified by the average of sodium concentrations over 48 h. Postoperative cerebral MRI was performed before hospital discharge. Results In our patient cohort, dysnatremia was present in 46 (13.5%) patients. Among them, hyponatremia occurred in 21 (6.2%) and hypernatremia in 25 (7.4%). When compared to patients with normonatremia, hyponatremia was not associated with EEG abnormalities and early adverse outcomes (Ps ≥ .14). In hypernatremia group, the CPB time was significantly longer and more frequent use of DHCA (Ps ≤ .049). After adjusting for time, CPB time and the use of DHCA, hypernatremia was significantly associated with worse EEG abnormalities (including background, seizures and pathological delta brushes), more severe brain injuries on MRI (Ps ≤ .04) and trended to be associated with longer postoperative mechanical ventilation time (P = .06). Conclusion Hypernatremia and hyponatremia were common in children after cardiac surgery. Hypernatremia, but not hyponatremia, was significantly associated with worse EEG abnormalities and more severe brain injuries on MRI and extended postoperative mechanical ventilation time.